2022
DOI: 10.1021/acs.langmuir.2c00086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acetaminophen on Molecular Adsorption and Transport Properties at Colloidal Liposome Surfaces Studied by Second Harmonic Generation Spectroscopy

Abstract: Time-resolved second harmonic generation (SHG) spectroscopy is used to investigate acetaminophen (APAP)-induced changes in the adsorption and transport properties of malachite green isothiocyanate (MGITC) dye to the surface of unilamellar 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) liposomes in an aqueous colloidal suspension. The adsorption of MGITC to DOPC liposome nanoparticles in water is driven by electrostatic and dipole–dipole interactions between the positively charged MGITC molecules and the zwitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…24,25 Conversely, a rise in signal can be attributed to an overall greater alignment of the molecules to one another in the membrane, 24,26 aggregation, 27,28 or a change in the local chemical environment. 29,30 Previous studies have demonstrated SHS and SHG can be used to quantify molecule-membrane interactions within model systems, [31][32][33][34][35][36][37][38][39][40] eukaryotic species, 16,[41][42][43][44] and bacterial cells. 24,25,[45][46][47][48][49][50][51][52][53][54][55][56] Specifically, we have implemented this technique to elucidate how structural moieties of small molecules facilitate its transport through the Gram-positive membranes of living S. aureus and Bacillus subtilis.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Conversely, a rise in signal can be attributed to an overall greater alignment of the molecules to one another in the membrane, 24,26 aggregation, 27,28 or a change in the local chemical environment. 29,30 Previous studies have demonstrated SHS and SHG can be used to quantify molecule-membrane interactions within model systems, [31][32][33][34][35][36][37][38][39][40] eukaryotic species, 16,[41][42][43][44] and bacterial cells. 24,25,[45][46][47][48][49][50][51][52][53][54][55][56] Specifically, we have implemented this technique to elucidate how structural moieties of small molecules facilitate its transport through the Gram-positive membranes of living S. aureus and Bacillus subtilis.…”
Section: Introductionmentioning
confidence: 99%
“…69 Because of the symmetry requirement for this process, interfaces and surfaces make ideal candidates to study with SHG as symmetry is inherently broken. SHG has previously been employed in many experiments to quantify the adsorption and transport kinetics of small molecules across the membranes of model systems, [70][71][72][73][74][75][76][77][78][79][80] living eukaryotic cells, [81][82][83][84][85] and live bacteria. 9, [86][87][88][89][90][91][92][93][94][95][96] As such, we have previously illustrated the membrane adsorption characteristics and subsequent behavior of the styryl dye molecules FM 2-10 and FM 4-64, within Enterococcus faecalis and S. aureus membranes with SHG and two-photon fluorescence.…”
Section: Introductionmentioning
confidence: 99%